2021
DOI: 10.1002/jso.26506
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced pseudomyxoma peritonei using cytoreductive surgery including total gastrectomy and perioperative chemotherapy

Abstract: Background: Pseudomyxoma peritonei is a disease caused by the widespread distribution of mucinous tumor into the peritoneal space from a perforated appendiceal neoplasm.Methods: All patients in this study had cytoreductive surgery with total gastrectomy plus perioperative intraperitoneal chemotherapy. A high diverting jejunostomy was used on all patients. Patient characteristics, adverse events, and survival were accumulated prospectively.Results: Fifty-eight patients were available for long-term follow-up. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A recent report showed that the univariate analysis of poor prognosis in patients with peritoneal pseudomyxoma after neoplasm reduction included women (P = 0.0127), intestinal obstruction before treatment (P = 0.00791) and PSS (P = 0.0054). There was also a significant difference in PSS in multivariate analysis (P = 0.0041) 14 . Our results suggested that male postoperative survival was worse, but it was not an independent factor for the prognosis.…”
Section: Discussionmentioning
confidence: 83%
“…A recent report showed that the univariate analysis of poor prognosis in patients with peritoneal pseudomyxoma after neoplasm reduction included women (P = 0.0127), intestinal obstruction before treatment (P = 0.00791) and PSS (P = 0.0054). There was also a significant difference in PSS in multivariate analysis (P = 0.0041) 14 . Our results suggested that male postoperative survival was worse, but it was not an independent factor for the prognosis.…”
Section: Discussionmentioning
confidence: 83%
“…Total gastrectomy has been described in the past as a requirement for complete cytoreduction 8,21 . If mucinous tumor cells entering through the Foramen of Winslow lodge in the cul‐de‐sac posterior to the gastric antrum, an antrectomy can be the procedure that facilitates the CC‐0/1 resection 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Total gastrectomy has been described as a necessary requirement of complete CRS in selected patients with appendiceal mucinous tumors. This was associated with a 10‐year survival of 58% 8 . Also, total abdominal colectomy (TAC) has been used in this group of patients to facilitate a complete cytoreduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by our data on prior surgical score, the interventions that occur prior to definitive cytoreductive surgery plus perioperative chemotherapy have a profound effect on outcome [13] . Sugarbaker and Chang showed that the most detrimental clinical feature for survival of a MAN patient requiring an extensive cytoreduction was a prior diagnosis of ovarian cancer [18] . These women had an error in diagnosis of ovarian cancer but, in reality had MAN.…”
Section: Discussionmentioning
confidence: 99%